Natural selection In Utero: Evidence from the great East Japan earthquake. Issue 4 (10th June 2013) - Catalano, R.; Yorifuji, T.; Kawachi, I.
<x xml:space="preserve">Abstract</x> Objectives Controversy remains over whether declines in male births reported after population stressors result from either or both reduced conception of males or increased selection in utero against male fetuses. We use monthly birth cohorts to determine if Japanese male births following the Great East Japan Earthquake of 2011 fell below levels expected from female births and from history (i.e., autocorrelation) among cohorts exposed to the Earthquake at or after conception. Methods We apply interrupted time‐series methods to 69 months (i.e., April, 2006 through December, 2011) of birth data from the most and least affected prefectures as well as from the remainder of Japan. We estimate expected male births from female births and from autocorrelation. Results Findings varied by distance from the greatest damage but suggest sensitive periods both early and late in gestation when population stressors may induce selection against males in utero. Support for reduced conception of males appeared only in the prefectures most damaged by the Earthquake. Conclusions Results align with the claim that natural selection has conserved mechanisms that reduce the odds of a male live birth during stressful times by reducing the conception of males and by increasing the rate of spontaneous abortion among male fetuses. Am. J. Hum. Biol. 25:555–559, 2013. © 2013 Wiley Periodicals, Inc.